Validity of Science Module Based on Problem Based Learning Multiple Representations to Improve Students' Higher Level Thinking Skills on the Topic of Acid-Base - Siti Sholikhah; Sentot Budi Rahardjo; Bowo Sugiharto (Jurnal Penelitian Pendidikan IPA, 2025)
The background of this research is the use of learning resources that have not been effective in improving students' higher-order thinking skills. This study aims to develop a science module, analyze its validity, feasibility, and effectiveness on higher order thinking skills. This research type of research and development (R&D) uses the 4D development model according to Thiagarajan (Define, Design, Develop, Disseminate). The science module was validated by six validators. The effectiveness of the module is seen from the increase in the students' higher order thinking skills test scores from 36 student. Validity was analyzed using Aiken's V, while effectiveness was analyzed with N-Gain. In the validation level, the learning material expert validator obtained a score of 0.91 with the category “valid”, the presentation expert validator obtained a score of 0.88 with the category “valid”, the linguist validation obtained a score of 0.91 with the category “valid”, and the graphic expert validation obtained a score of 0.88 with the category “valid”. A feasibility value of 79.8 by teachers with a feasible category. The effectiveness results show that the module has an effect on students' higher order thinking skills  as evidenced by the N-Gain score of the experimental class of 0,63 with a fairly effective category while the N-Gain score of the control class is 0,55 with a less effective category. Thus, the developed e-module is declared valid, feasible, and effective.